Проблематика розробки мультисервісної платформи для аналітики успішності спортсменів - Побізінський, О. М. (ХНУРЕ, 2025)
Developing a multi-service platform for analyzing athletes’ performance is a complex process that involves integrating heterogeneous data from various sources, such as wearable devices, GPS trackers, medical sensors, and social media. The main challenges include efficiently processing large amounts of data, ensuring reliable protection of athletes’ personal data, and adapting the platform to different user groups. The use of machine learning and artificial intelligence methods helps to identify patterns and predict results, but requires a high-quality training dataset. Data visualization is a critical aspect, as the results should be understandable for athletes, coaches, and sports doctors. Implementing the platform in the sports process requires training and gradual adaptation of the system.
Keywords: спортсмен; мультисервісна платформа